Inequality and Income Structure: A Case Study on Maize Farmer Household in Gorontalo Regency - Mahludin H. Baruwadi; Fitri Hadi Yulia Akib; Echan Adam (State University of Gorontalo, 2022)
The present work aims to investigate 1) the inequality and income structure of maize farmers’ households; and 2) the contribution of maize farming to the household income of the farmer. Furthermore, this research was conducted in Gorontalo Regency for four months. It relied on the survey method, in which the data were collected from questionnaires and interviews. The data consisted of primary data from 132 maize farmers randomly selected from each area using the proportional allocation method. All data were analyzed using the quantitative descriptive method, Gini coefficient, and z-test for proportions. According to the results, moderate inequality was caused if the household income was from maize farming and other farming. The inequality would be categorized high if the non-farming income was included in the calculation. Based on the income structure, this inequality was likely to occur since the non-farming income contributed significantly to the percentage of the total income of high-income farmers. Maize farming income was significant to the farmers’ household income, meaning that farmers relied on maize farming as their primary income source.